Lecturers And Students Responses Toward The Program Of Independent Learning-Independent Campus (MBKM) - Dwi Fauziansyah Moenardy; Denny Saputera; Rina Ariyanti Dewi; Aminudin; Della Dwinanti Sumpena; Soni A. Nulhaqim (Universitas Widyatama, 2022)
Independent Learning – Independent Campus (MBKM) is one of the policies from the Minister of Education, Culture, Research, and Technology, Mr. Nadiem Makarim. One of the programs of the Independent Learning – Independent Campus policy is the Right to Study for Three Semesters Outside the Study Program. Independent Campus is part of the Independent Learning policies from the Indonesian Minister of Education, Culture, Research, and Technology that provides opportunities for students to enhance their competencies according to their talents and interests by directly exploring the industrial or professional world as the groundwork for their future careers. There are eight forms of learning activities in accordance with Permendikbud No. 3 of 2020 Article 15 paragraph 1 that can be carried out within the study program or outside the study program, such as: student exchange, internship/work practice, teaching assistant in an educational unit, research, humanitarian projects, entrepreneurial activities, independent project/study, build villages/thematic community service program. When the students carry out the Independent Learning – Independent Campus (MBKM) programs, the results will be recognized as equivalent to 20 credit in each semester. To analyze how far the MBKM program has been socialized and understood by lecturers, students and universities, the Ministry of Education conducted a survey. The method used in the survey is census and the research method used in the analysis is qualitative research method. Based on the result, there are 7 lecturers out of 15 lecturers from the Faculty of Social Science and Political Science Widyatama University (3 study program) who have filled out the survey form. 8 lecturers cannot fill out the survey form because their NIDN are not issued yet. There are also 14 students from the class of 2020 who have filled out the survey form, while the class of 2021 cannot fill out the form because their names are not listed in the Directorate General of Higher Education (PDPT DIKTI) yet